Host Langerin (CD207) is a receptor for Yersinia pestis phagocytosis and promotes dissemination. Issue 9 (21st April 2015) - Yang, Kun; Park, Chae G; Cheong, Cheolho; Bulgheresi, Silvia; Zhang, Shusheng; Zhang, Pei; He, Yingxia; Jiang, Lingyu; Huang, Hongping; Ding, Honghui; Wu, Yiping; Wang, Shaogang; et al.
Abstract : Yersinia pestis is a Gram‐negative bacterium that causes plague. After Y. pestis overcomes the skin barrier, it encounters antigen‐presenting cells (APCs), such as Langerhans and dendritic cells. They transport the bacteria from the skin to the lymph nodes. However, the molecular mechanisms involved in bacterial transmission are unclear. Langerhans cells (LCs) express Langerin (CD207), a calcium‐dependent (C‐type) lectin. Furthermore, Y. pestis possesses exposed core oligosaccharides. In this study, we show that Y. pestis invades LCs and Langerin‐expressing transfectants. However, when the bacterial core oligosaccharides are shielded or truncated, Y. pestis propensity to invade Langerhans and Langerin‐expressing cells decreases. Moreover, the interaction of Y. pestis with Langerin‐expressing transfectants is inhibited by purified Langerin, a DC‐SIGN (DC‐specific intercellular adhesion molecule 3 grabbing nonintegrin)‐like molecule, an anti‐CD207 antibody, purified core oligosaccharides and several oligosaccharides. Furthermore, covering core oligosaccharides reduces the mortality associated with murine infection by adversely affecting the transmission of Y. pestis to lymph nodes. These results demonstrate that direct interaction of core oligosaccharides with Langerin facilitates the invasion of LCs by Y. pestis . Therefore, Langerin‐mediated binding of Y. pestis to APCs may promote its dissemination and infection.